Comparative Study of Hematological-biochemical Parameters in Indigenous Sheep Reared in Semi-Desert and Mountainous Areas of Libya - Nagia Abdalsalam; Hazawy, Safia (AlQalam Journal of Medical and Applied Sciences, 2025)
This study aimed to investigate specific hematological parameters in indigenous populations. Libyan sheep are raised under two contrasting ecological zones: semi-desert and highland regions. Blood profiles provide essential information regarding overall health conditions and adaptive mechanisms of animals in response to environmental challenges. A total of 50 apparently healthy adult female sheep (25 from each region) were examined. Blood samples were collected and analyzed for red blood cell count (RBC), white blood cell count (WBC), hemoglobin concentration (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), platelet count (PLT), Calcium (Ca), Phosphorus (P), and Total protein (TP). Significant differences (p-value < 0.05) were observed between groups. Highland sheep exhibited higher RBC, Hb, MCV, MCH, MCHC, and PLT values, while semi-desert sheep showed higher WBC count. These findings demonstrate the influence of environmental conditions such as altitude and temperature on the hematological profile of sheep, contributing to understanding their physiological adaptation.